Strategi Kepemimpinan Kepala KUA dalam Meningkatkan Kedisplinan Pegawai pada Kantor Urusan Agama (KUA) di Desa Napa Kecamatan Batangtoru - Subuh Waldo Huakbar (Yayasan Al-Ahliyah Al-Islamiyah Aek Badak, 2024)
Employee discipline can be seen as a kind of training intended to shape and improve employee knowledge, attitudes, and behavior to encourage other staff members to take an active role in raising their performance standards. The purpose of this research is to determine the leadership approach used by the head of the KUA Office of Religious Affairs in Napa Village, Batangtoru District in improving employee discipline. This research is qualitative in descriptive form. What this means is that the research conducted seeks to understand phenomena such as motivation, behavior, and perceptions encountered by study participants. The motivation for this research stems from the researcher's interest in the leadership approach of the head of the KUA in improving the discipline of employees at the Napa Village Religious Affairs Office, Batangtoru District. Research results: The Head of the KUA of Napa Village, Batangtoru District, uses three strategies to improve employee discipline, namely by giving instructions to employees, giving them examples, and holding sharing sessions. The first three supporting criteria are: (1) effective leadership; (2) receive compensation; and (3) punishment. The first two barriers are a lack of personal awareness and work procrastination.